À flor da pele: uma análise crítica de discursos empresariais sobre diversidade racial no trabalho - Mara Marcal Sales (2012)
The present qualitative research has sought to analyze the discourses on fostering practices of racial diversity on work, published on the internet by companies acting in Brazil, in order to identify the discursive precepts and articulations bound to them. The development of the research was subsided by the critical discourse analysis, from the buoyage proposed by Fairclough (2001). For such, the study addressed, initially, the articulations that approach the themes of race and work in Brazil. Through the review of the theoretical production concerning the referred themes, three aspects have been highlighted. The first side addressed the scope and importance of the presence of black people on the labour field already from the enslavement. Next, we approached the implications arising from prejudice, racial discrimination and racism factors that concur decisively to the fact that the Brazilian black populations occupy mostly charges of less prestige of and less remuneration. And, thirdly, we have analysed the affirmative actions in benefit of diversity. In relation to the former, we sought to delineate the context that made the black social movements encompass as his main claim today and intended to see them spread out also to the work field. The analysis of the constitution of diversity fostering actions, by its turn, pointed that the plurality and the difference have been exhaustingly incorporate to the roll of business discourses. Have raised the theoretical aspects, we proceed to the documental analysis that took as the corpus texts that versed on the theme of diversity and that were retrieved from companies sites. The carrying of the analysis was supported by the conception presented by Fairclough (2001) which takes the discourse as a social practice, a way of action on the world. This way, the discourses found on the sites denote the expansion of the radius of action of companies try to be present in different harvest, at the same time they search to present as ethic organizations. The treatment dispensed to diversity is guided by interdiscursive elements that emphasize the image of the organizations as an organism compromised with ideas of social harmony. Through the lexical choices and the argumentation presented, the companies present diversity as an instrument capable of contributing to the productive potentiation. The present of the difference is thus valued as strategic condition for insertion in the globalized markets.